2020
DOI: 10.1021/acs.jpcc.9b11291
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Al2O3Using Trimethylaluminum and H2O: The Kinetics of the H2O Half-Cycle

Abstract: Atomic layer deposition (ALD) of Al 2 O 3 using trimethylaluminum and H 2 O is known to proceed through sequential surface reactions that leave the surface alternately terminated with AlCH 3 and OH groups. Using in situ reflection− absorption infrared spectroscopy in a flow reactor, we monitor the consumption of AlCH 3 groups by brief pulses of H 2 O at temperatures between 105 and 300 °C. At low temperatures, the surface reactions occur by what appears to be two stages that can be fit to a biexponential decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…The BB-SFG signal is proportional to the coverage and not to the change in coverage as is the case for, e.g ., FTIR difference spectra, which rules out any persistent CH 3 species after the O 2 exposure as having been seen for other ALD processes. 31 , 45 , 46 Not all CH 3 groups undergo complete dehydrogenation in the precursor half-cycle since Figures 4 and 8 show clear evidence of CH 3 on the surface at the end of the precursor half-cycle. The temperature has a strong impact on the relative amounts of the surface species at the end of the precursor half-cycle: Figure 8 shows that the amount of C=C is fairly constant, while the CH 3 coverage decreases with temperature.…”
Section: Discussionmentioning
confidence: 98%
“…The BB-SFG signal is proportional to the coverage and not to the change in coverage as is the case for, e.g ., FTIR difference spectra, which rules out any persistent CH 3 species after the O 2 exposure as having been seen for other ALD processes. 31 , 45 , 46 Not all CH 3 groups undergo complete dehydrogenation in the precursor half-cycle since Figures 4 and 8 show clear evidence of CH 3 on the surface at the end of the precursor half-cycle. The temperature has a strong impact on the relative amounts of the surface species at the end of the precursor half-cycle: Figure 8 shows that the amount of C=C is fairly constant, while the CH 3 coverage decreases with temperature.…”
Section: Discussionmentioning
confidence: 98%
“…The thickness of the as-deposited thin film can be adjusted precisely at the atomic scale by the total number of ALD cycles. [110,111] Hyde et al [112] and Waldman et al [113] utilised the ALD of alumina to introduce surface hydrophilicity to the initially hydrophobic polypropylene (PP) membranes. Nikkola et al [114] utilised a similar procedure for enhancing hydrophilicity and therefore the anti-fouling capacity of thin film composite (TFC) polyamide (PA) reverse osmosis (RO) membranes.…”
Section: Ald-enabled Roughness Controllingmentioning
confidence: 99%
“…The latter argument was given as well by Sperling et al, explaining the double exponential decay of surface CH 3 groups observed by in situ infrared spectroscopy during the water pulse. 8 This was solved tentatively by introducing a coverage-dependent activation energy. It seems that, after all, the TMA-water process is not as ideal as generally believed.…”
Section: Introductionmentioning
confidence: 99%